How common is chronic fatigue syndrome; how long is a piece of string? - White Peter D (BMC, 2007)
Abstract Commentary on Prevalence of chronic fatigue syndrome in metropolitan, urban, and rural Georgia William C Reeves, James F Jones, Elizabeth Maloney, Christine Heim, David C Hoaglin, Roumiana S Boneva, Marjorie Morrissey and Rebecca Devlin